2012
DOI: 10.1371/journal.pone.0034014
|View full text |Cite
|
Sign up to set email alerts
|

A Single Gene Target of an ETS-Family Transcription Factor Determines Neuronal CO2-Chemosensitivity

Abstract: Many animals possess neurons specialized for the detection of carbon dioxide (CO2), which acts as a cue to elicit behavioral responses and is also an internally generated product of respiration that regulates animal physiology. In many organisms how such neurons detect CO2 is poorly understood. We report here a mechanism that endows C. elegans neurons with the ability to detect CO2. The ETS-5 transcription factor is necessary for the specification of CO2-sensing BAG neurons. Expression of a single ETS-5 target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 40 publications
4
73
0
Order By: Relevance
“…The ASG neurons are also able to act in stress conditions when they are recruited to a novel neuronal circuit to enable an escape response (52). In contrast, the BAG neurons function to detect changes in oxygen and carbon dioxide in the environment and to coordinate behavioral responses according to changes in environmental gas status (26,(53)(54)(55)(56). Our behavioral state analysis shows that the ASG and BAG neurons are both important for the inhibition of quiescence under standard laboratory conditions, whereas the ASG neurons potentially play a more major role in the inhibition of roaming behavior.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ASG neurons are also able to act in stress conditions when they are recruited to a novel neuronal circuit to enable an escape response (52). In contrast, the BAG neurons function to detect changes in oxygen and carbon dioxide in the environment and to coordinate behavioral responses according to changes in environmental gas status (26,(53)(54)(55)(56). Our behavioral state analysis shows that the ASG and BAG neurons are both important for the inhibition of quiescence under standard laboratory conditions, whereas the ASG neurons potentially play a more major role in the inhibition of roaming behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional targets of ETS-5 in the ASG and BAG neurons have not been fully described; however, previous studies have shown that specific FMRFamide-related neuropeptides, expressed in the BAG neurons (FLP-13 and FLP-19), are regulated by ETS-5 (26,27). Therefore, we examined the behavior of mutant strains lacking these neuropeptides, and found that loss of both flp-13 and flp-19 caused a partial decrease in exploratory capacity.…”
Section: Neuropeptide Signaling Contributes To the Control Of Exploramentioning
confidence: 95%
See 3 more Smart Citations